2021
DOI: 10.1177/17474930211008701
|View full text |Cite
|
Sign up to set email alerts
|

Drip-and-ship versus mothership for endovascular treatment of acute stroke: A comparative effectiveness analysis

Abstract: Background Triage for suspected acute stroke has two main options (1) transport to the closest primary stroke center (PSC) and then to the nearest comprehensive stroke center (CSC) (Drip-and-Ship) or (2) transport the patient to the nearest CSC, bypassing a closer PSC (mothership). The purpose was to evaluate the effectiveness of drip-and-ship versus mothership models for acute stroke patients. Methods A Markov decision-analytic model was constructed. All model parameters were derived from recent medical li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Despite many efforts to speed up and optimise acute stroke patient management, still only 0.8-1.3% of acute ischaemic stroke (AIS) patients receive their intravenous thrombolysis (IVT) within the so-called golden hourthe first 60 min after symptom onset, when chances of full recovery are highest. 1,2 Many reports on stroke scales, [3][4][5][6][7] emergency medical service (EMS) training and educational programmes, [8][9][10][11][12] structured EMS pre-notification to hospital stroke teams, [13][14][15] emergency department streamlining [16][17][18][19][20] and different triage pathways (mothership vs drive the doctor vs drip and ship) [21][22][23][24][25][26][27][28][29][30][31] have all demonstrated an improvement of treatment numbers and times, but timely delivery of the available and highly beneficial reperfusion therapies [IVT and mechanical thrombectomy (MT)] to AIS patients is still underachieved. Furthermore, delays in onset to treatment times correlate to longer bolus to reperfusion times in AIS patients with proximal intracranial occlusions treated with IVT.…”
Section: Introductionmentioning
confidence: 99%
“…Despite many efforts to speed up and optimise acute stroke patient management, still only 0.8-1.3% of acute ischaemic stroke (AIS) patients receive their intravenous thrombolysis (IVT) within the so-called golden hourthe first 60 min after symptom onset, when chances of full recovery are highest. 1,2 Many reports on stroke scales, [3][4][5][6][7] emergency medical service (EMS) training and educational programmes, [8][9][10][11][12] structured EMS pre-notification to hospital stroke teams, [13][14][15] emergency department streamlining [16][17][18][19][20] and different triage pathways (mothership vs drive the doctor vs drip and ship) [21][22][23][24][25][26][27][28][29][30][31] have all demonstrated an improvement of treatment numbers and times, but timely delivery of the available and highly beneficial reperfusion therapies [IVT and mechanical thrombectomy (MT)] to AIS patients is still underachieved. Furthermore, delays in onset to treatment times correlate to longer bolus to reperfusion times in AIS patients with proximal intracranial occlusions treated with IVT.…”
Section: Introductionmentioning
confidence: 99%
“…There is still ongoing debate as to which model of pre-hospital care (mothership or drip-and-ship model) offers better outcomes and regional differences might play an important role in choosing either model [16][17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have compared outcomes from the use of the drip-and-ship and mothership models, and, although most seem to favor the mothership approach (particularly, due to higher functional independence), regional differences in geography and healthcare organization make it difficult to understand the benefit for each country and region [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…In search of the optimal referral strategy, a modelling study of 242 874 emergency admissions in England showed that most of the inhabitants of England would gain the greatest clinical benefit from direct conveyance to a stroke centre capable of administering IAT, although the study also discussed the real-life feasibility of such an approach given the potential destabilization of the EMS system [8]. Another modelling study focusing on healthcare economics concluded that the ‘drip and ship’ approach may have a slight advantage over the ‘mothership’ approach in regard to expected costs [9]. In general, the answer to ‘drip and ship’ remains unclear and more research is required to understand the preferred approach for a specific region.…”
Section: Referral Models For Acute Stroke Drip and Ship Vs Mothershipmentioning
confidence: 99%
“…Future research may clarify the role of prehospital delivery of treatments, such as new neuroprotectants and treatments to prevent haematoma enlargement. Another modelling study focusing on healthcare economics concluded that the 'drip and ship' approach may have a slight advantage over the 'mothership' approach in regard to expected costs [9]. In general, the answer to 'drip and ship' remains unclear and more research is required to understand the preferred approach for a specific region.…”
Section: Key Pointsmentioning
confidence: 99%